Combating immunosuppression in glioma. (June 2008) - Vega, Eleanor A; Graner, Michael W; Sampson, John H
Despite maximal therapy, malignant gliomas have a very poor prognosis. Patients with glioma express significant immune defects, including CD4 lymphopenia, increased fractions of regulatory T cells in peripheral blood and shifts in cytokine profiles from Th1 to Th2. Recent studies have focused on ways to combat immunosuppression in patients with glioma as well as in animal models for glioma. We concentrate on two specific ways to combat immunosuppression: inhibition of TGF-ββ signaling and modulation of regulatory T cells. TGF-ββ signaling can be interrupted by antisense oligonucleotide technology, TGF-ββ receptor I kinase inhibitors, soluble TGF-ββ receptors and antibodies against TGF-ββ. Regulatory T cells have been targeted with antibodies against T-cell markers, such as CD25, CTLA-4 and GITR. In addition, vaccination against Foxp3 has been explored. The results of these studies have been encouraging; combating immunosuppression may be one key to improving prognosis in malignant glioma.